Differentiation and Risk-Aversion in Imperfectly Competitive Labor Markets - Christina E. Bannier; Eberhard Feess; Natalie Packham; Markus Walzl (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
This paper examines the effect of imperfect labor market competition on the efficiency of compensation schemes in a setting with moral hazard and risk-averse agents who have private information on their ability. Two heterogenous firms - characterized by vertical, respectively horizontal, differentiation - compete for agents by offering contracts with fixed and variable payments. The degree of competition then determines the structure of these contracts. Three regions can be distinguished: For low competition, low-ability agents are under-incentivized and exert too little effort. For high competition, high-ability agents are over-incentivized and bear too much risk. For a range of intermediate degrees of competition, however, agents' private information has no impact and contracts are second-best. An equilibrium where both firms are active exists only when the least-cost separating allocation (LCS) is interim efficient. If firms are only vertically differentiated, then the inferior firm is inactive in equilibrium, but its competitive threat still generates the three regions just described. Moreover, an equilibrium in which the inferior firm would not break even when attracting both agent types may exist even when the LCS is not interim efficient. We show that the degrees of vertical and horizontal differentiation have opposite impacts on the condition for interim efficiency of the LCS.
Keywords: D82; D86; J31; J33; 330; Incentive compensation; screening; imperfect labor market competition; vertical differentiation; horizontal differentiation; risk aversion